PERFIL E CONDIÇÕES DE SAÚDE DE IDOSOS QUE PARTICIPAM DE GRUPOS DE CONVIVÊNCIA - Hildbrandt, Leila M.; Franco, Gianfabio P.; Silva, Luiz A. A. d.; Jahn, Alice D. C.; Winck, Marisa T.; Carli, Rafaela d.; Heisler, Elisa V. (Salão do Conhecimento, 2013)
Resumo